Fictions from an orphan state literary reflections of Austria between Habsburg and Hitler - Barker, Andrew 1947- (Boydell & Brewer, 2012)
The literary flair of fin-de-siècle Vienna lived on after 1918 in the First Austrian Republic even as writers grappled with the consequences of a lost war and the vanished Habsburg Empire. Reacting to historical and political issues often distinct from those in Weimar Germany, Austrian literary culture, though frequently associated with Jewish writers deeply attached to the concept of an independent Austria, reflected the republic's ever-deepening antisemitism and the growing clamor for political union with Germany. Spanning the two momentous decades between the fall of the empire in 1918 and the Nazi 'Anschluss' in 1938, this book explores work by canonical writers such as Schnitzler, Kraus, Roth, and Werfel and by now-forgotten figures such as the pacifist Andreas Latzko, the arch-Nazi Bruno Brehm, and the fervently Jewish Soma Morgenstern. Also taken into account are Ernst Weiss's 'Hitler' novel 'Der Augenzeuge' and 1930s works about First Republic Austria by the German Communist writers Anna Seghers and Friedrich Wolf. Andrew Barker's book paints a varied and vivid picture of one of the most challenging and underresearched periods in twentieth-century cultural history. Andrew Barker is Emeritus Professor of Austrian Studies at the University of Edinburgh, Scotland